Implementation of Conditional Moment Closure using the Taylor Expansion and Finite Differences - M. M., Noor; T. F., Yusaf (2011)
Current stringent rules for pollution release to the atmosphere have led to researchers worldwide developing methods to increase the efficiency of combustion. In order to reduce experimental cost, accurate modelling and simulation is a very critical step. One combustion model is Conditional Moment Closure (CMC). This paper reports a preliminary result implementing the CMC model using a finite difference method. The Taylor series expansion was utilised to determine the error term for the discretization. FORTRAN code was used to simulate the discretized partial differential equation. From the simulation result, it is found that the explicit method is simple but less accurate than the implicit method.